2001
DOI: 10.1055/s-2001-10753
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation von Eltern an eine chronische Erkrankung ihres Kindes nach der Diagnosestellung

Abstract: The course and the adaptivity of parental coping with a chronical disease in their child (leukemia, solid tumors, diabetes or epilepsy) was studied during the first three months after diagnosis. 66 parents answered questionnaires to their coping and their quality of life as well as to the perceived quality of life of their children 1-2 weeks and again 8-12 weeks after diagnosis. As coping was stable, the parents' and children's quality of life increased over time. Coping strategies using communication and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…These findings are consistent with the literature, describing a tendency to utilize intra-family resources in case of chronic childhood disease. 36 On average, the parents described only minor restrictions in the quality of life of their children. This might because most of our cohort was deemed to have only mild cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the literature, describing a tendency to utilize intra-family resources in case of chronic childhood disease. 36 On average, the parents described only minor restrictions in the quality of life of their children. This might because most of our cohort was deemed to have only mild cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…We assume the time since diagnosis might be decisive for the parental HrQoL. At the time of the study, the mean age of the CAH children diagnosed by newborn screening was 11.01 years, whereas the cited study was performed during the first three months after diagnosis [47]. It has been shown that HrQoL increased over time [43].…”
Section: Discussionmentioning
confidence: 99%
“…Motivation, finanzielle Hilfe, Zeitressourcen für krankheitsbezogene Aufgaben, Informationsrecherche, Beratungsaktivitäten). Diese umfangreiche Bereitstellung der psychosozialen Ressourcen kann auf die Komplexität der kausalen Belastungen durch die Neoplasie (körperlich, emotional, sozial) zurückgeführt werden, was Goldbeck et al [13] bestätigen.…”
Section: Ergebnisseunclassified